2024
DOI: 10.1021/acs.joc.3c02445
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acid/Palladium Hybrid Catalysis for Regioselective O-Allylation of Carbohydrates

Yuki Nakamura,
Kazuma Irisawa,
Kazuishi Makino
et al.

Abstract: Novel imidazole-containing boronic acid and palladium hybrid catalysis for regioselective O-allylation of carbohydrates has been developed. This catalytic process enables the introduction of a useful allyl functional group into the equatorial hydroxy group of cis-1,2-diols of various carbohydrates with low catalyst loading and excellent regioselectivities. This is the first report on hybrid catalysis in combination with a Lewis base-containing boronic acid and a transition metal complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…By employing allylic alcohols as the electrophiles in the presence of a palladium bis­(phosphine) cocatalyst, regioselective dehydrative N-allylations of various azoles were achieved (Scheme ). Control experiments showed that the organoboron catalyst has a significant effect on both reaction rate and N-allylation regioselectivity, suggesting that it plays a role both in activating the allylic alcohol electrophile, in cooperation with the Xantphos­(Pd) complex, and the azole nucleophile. , The allylation method has been extended to other NH-pronucleophiles, including pyridones and sulfoximines …”
Section: Introductionmentioning
confidence: 99%
“…By employing allylic alcohols as the electrophiles in the presence of a palladium bis­(phosphine) cocatalyst, regioselective dehydrative N-allylations of various azoles were achieved (Scheme ). Control experiments showed that the organoboron catalyst has a significant effect on both reaction rate and N-allylation regioselectivity, suggesting that it plays a role both in activating the allylic alcohol electrophile, in cooperation with the Xantphos­(Pd) complex, and the azole nucleophile. , The allylation method has been extended to other NH-pronucleophiles, including pyridones and sulfoximines …”
Section: Introductionmentioning
confidence: 99%